O incumprimento no crédito à habitação e a diminuição do risco na entrega da casa - Gonçalves, João Gama (2018)
Mortgage lending is of particular relevance in Portugal, not only at a social level, as it represents the main source of indebtedness of Portuguese households, but also at the level of the financial sector, with a significant weight in credit institutions’ balance sheets. This dissertation focuses on its credit default and on the foreclosure mechanisms available to credit institutions for debt repayment (even after the delivery of the relevant mortgaged real estate) and analyzes the current solutions aiming at the mitigation of the risks associated with this type of credit, presenting alternative solutions that could be effective in reducing the aforementioned risk.